Юридична відповідальність як явище об’єктивного права - Калєніченко, Л. І.; Kalenichenko, L. I.; Калєніченко Лідія Іванівна (Право і Безпека. - 2016. - № 2 (61). - С. 31-37, 2016)
Проаналізовано особливості конституційно-правової, кримінальної, адміністративної, цивільно-правової відповідальності як явищ об’єктивного права. Встановлено основні риси юридичної відповідальності як явища об’єктивного права. Сформульовано дефініцію юридичної відповідальності як явища об’єктивного права.

The features of constitutional and legal, criminal, administrative, civil and legal liability as a phenomenon of objective law have been analyzed. It has been established that legal liability as a phenomenon of objective law is characterized by certain features: 1) has an abstract form; 2) is not personalized; 3) is formally expressed in sanctions of the relevant norms of law branches; 4) is based on state compulsion (closely connected with the state); 5) causes some negative results (of personal, property, organizational nature) for a person, who has committed an offense; 6) has a procedural form of implementation (with the legislation of Ukraine there is a certain order, sequence of actions prescribed for the onset of legal liability); 7) has grounds defined by the law. The author has formulated a definition of legal liability as a phenomenon of objective law – it is law norms provided by the sanctions, granted by the ability to use the state compulsion, adverse effects of personal, property or organizational nature, which are suffered by the relative law subject for the commission of an offense (violation of subjective rights), and which are procedurally enshrined in the legislation.

Проанализированы особенности конституционно-правовой, уголовной, административной, гражданско-правовой ответственности как явлений объективного права. Установлены основные черты юридической ответственности как явления объективного права. Сформулирована дефиниция юридической ответственности как явления объективного права.
Legal liability as a phenomenon of objective law
Юридическая ответственность как явление объективного права
Keywords: Держава і право. State and Law. Государство и право; Наукові публікації. Scientific publications. Научные публикации; відповідальність; юридична відповідальність; конституційно-правова відповідальність; кримінальна відповідальність; адміністративна відповідальність; цивільно-правова відповідальність; liability; legal liability; constitutional and legal liability; criminal liability; administrative liability; civil and legal liability; ответственность; юридическая ответственность; конституционно-правовая ответственность; уголовная ответственность; административная ответственность; гражданско-правовая ответственность